Decorating g-C3N4 with alkalinized Ti3C2 MXene for promoted photocatalytic CO2 reduction performance - Tang, Qijun; Sun, Zhuxing; Deng, Shuang; Wang, Haiqiang; Wu, Zhongbiao (Journal of colloid and interface science, 2020)
[Display omitted] Photocatalytic reduction of carbon dioxide (CO2) under visible light irradiation for producing high-value fuel has attracted tremendous attention in recent years. In this study, titanium carbide MXene (Ti3C2) was used as a noble metal-free co-catalyst by simply mixing graphitic carbon nitride (g-C3N4) and alkalized Ti3C2. The carbon monoxide evolution rate of the optimized composite (5%TCOH-CN) from photocatalytic reduction of CO2 was 5.9 times higher than that of pure g-C3N4. Alkalized Ti3C2 was responsible for the superior photocatalytic activity due to its excellent electrical conductivity and large CO2 adsorption capacity. Furthermore, the separation of the photo-induced electron–hole pairs was greatly enhanced because of the large Fermi level difference between alkalized Ti3C2 and pure g-C3N4. This work demonstrates the potential of MXenes as noble metal-free co-catalyst for photocatalysis processes such as carbon dioxide reduction reaction and nitrogen reduction reaction.